2004
DOI: 10.1161/01.cir.0000117254.68497.39
|View full text |Cite
|
Sign up to set email alerts
|

Altered Calcium Handling Is Critically Involved in the Cardiotoxic Effects of Chronic β-Adrenergic Stimulation

Abstract: Background-Chronic adrenergic stimulation leads to cardiac hypertrophy and heart failure in experimental models and contributes to the progression of heart failure in humans. The pathways mediating the detrimental effects of chronic ␤-adrenergic stimulation are only partly understood. We investigated whether genetic modification of calcium handling through deletion of phospholamban in mice would affect the development of heart failure in mice with transgenic overexpression of the ␤ 1 -adrenergic receptor. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 37 publications
1
65
0
Order By: Relevance
“…This increase in intracellular Ca 2+ probably is caused by a direct coupling of the α subunit of the stimulatory heterotrimeric guanine nucleotide-binding G protein to the Ca 2+ channel (25). Cardiomyopathic changes in ß 1 -adrenoceptoroverexpressing transgenic animals also could be rescued by phospholamban ablation which normalizes diastolic calcium levels (26), confirming that increased intracellular Ca 2+ is critical for the detrimental effects of β 1 -adrenergic stimulation (27). Our present study showed that β 1 -EC II IgG increased CaMKII phosphorylation and myocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in intracellular Ca 2+ probably is caused by a direct coupling of the α subunit of the stimulatory heterotrimeric guanine nucleotide-binding G protein to the Ca 2+ channel (25). Cardiomyopathic changes in ß 1 -adrenoceptoroverexpressing transgenic animals also could be rescued by phospholamban ablation which normalizes diastolic calcium levels (26), confirming that increased intracellular Ca 2+ is critical for the detrimental effects of β 1 -adrenergic stimulation (27). Our present study showed that β 1 -EC II IgG increased CaMKII phosphorylation and myocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In marked contrast to results obtained from β 2 -subtype that needs a high level of expression to develop of heart failure, mice overexpressing β 1 -subtype, as low as five fold the endogenous expression level, present progressive hypertrophy and ventricular dysfunction, which culminate with heart failure by the age of 35 weeks (Engelhardt et al 1999). The pathways mediating the cardiac deleterious effects of β 1 -subtype overexpression seems to involve an altered calcium handling (Engelhardt et al 2001(Engelhardt et al , 2004) and increased Na + -H + exchanger (Engelhardt et al 2002). In addition, overexpression of β 1 -subtype in mice leads to upregulation of pro-apoptotic proteins, such as Bax (Bisognano et al 2000), and chronic stimulation of β 1 -subtype has been shown to increase rate of apoptosis (Communal et al 1998, Xiao 2001, Zhu et al 2001.…”
Section: Adrenergic Receptorsmentioning
confidence: 92%
“…25 These properties of MCT-rats are consistent with past reports for the same experimental model 27,28 and for other animal models of ventricular hypertrophy. 29 Thus, we are convinced that MCT-rats can serve as a model of ventricular hypertrophy to examine the propagation features of Ca 2+ waves.…”
Section: Mct-induced Rv Hypertrophymentioning
confidence: 94%